Positioning the Private Health Facilities Towards Continuous Service Provision During the COVID-19 Pandemic - Olayinka Ilesanmi; Aanuoluwapo Afolabi (Baqiyatallah University of Medical Sciences, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has triggered an increased demand for health services. Public health facilities are becoming increasingly inadequate to provide care for the increasing COVID-19 cases. Therefore, positioning the private health facilities (PHFs) to contribute to the COVID-19 outbreak response is highly required. To position PHFs for an improved COVID-19 outbreak response, guidelines that provide clarity on the role of PHF in the COVID-19 outbreak response need to be developed. Specific regulations should be tailored towards the government acting as a financial risk protector for PHF. Also, equity in the distribution of personal protective equipment (PPE) across the public and PHF from the Federal Government should be ensured. Moreover, subsidies should be provided on PPE, including goggles, hand sanitizers, and face masks. Furthermore, the purchase of PPE could be made by PHF on a large scale at subsidized costs via the PHF professional bodies and associations. Moreover, a comprehensive assessment of the human and infrastructural capacity of PHF needs to be conducted regarding the COVID-19 response. Results obtained from such assessment would inform on the existing human resources needs of the private sector and opportunities by which PHF's capacity could be enhanced. In addition, assessing the extent of representativeness of PHF in the existing rapid response team needs to be conducted. All challenges delimiting the active involvement of the PHF should be addressed. Additionally, adequate support systems need to be developed and well-placed to promote the involvement of the PHF in the outbreak response.